INTEGRASI PENDEKATAN MULTIDISIPLINER, INTERDISIPLINER, DAN TRANSDISIPLINER DALAM PENDIDIKAN ISLAM - Musyahid; Kumalasari, Eva; Wathoni, Kharisul (Institut Agama Islam Sahid (INAIS) Bogor, 2025)
Islamic education faces complex challenges in the digital and globalized era, requiring approaches that integrate traditional values with contemporary needs. This study aims to describe, critique, and propose implications for implementing multidisciplinary, interdisciplinary, and transdisciplinary approaches in Islamic education. A qualitative literature review method was employed to explore the integration of various disciplines into the Islamic education curriculum, with content analysis applied for data analysis. Findings indicate that these approaches can enrich the understanding and relevance of Islamic education by facilitating a more comprehensive and adaptive understanding of contemporary changes. However, challenges such as a lack of educator training and resistance to change need to be addressed to maximize the potential of these approaches. Regular evaluation and collaborative support among academics, practitioners, and policymakers are necessary to ensure the successful implementation and relevance of the curriculum.